Freedom and Globalization - Kwiek, Marek (My University, 2002)
Social sciences have to adapt themselves conceptually to the new world in which, perhaps, the nation-state may not be playing the decisive role traditionally ascribed to it by modernity. The globalizing world may require a brand new theory of the state and a renewed theory of freedom and democracy in a situation in which the nation-state, although has not disappeared and surely will not disappear, but nevertheless becomes weaker and weaker in its confrontation with new global political entities such as e.g. supranational political entities, or in its confrontation with international organizations, transnational corporations, non-governmental and independent system of commercial arbitration, ratings provided by international rating agencies or with limitations of various military, political and economic treaties and unions. In the face of the unavoidable, as it seems, giving (at least some) way to new political players (including transnational corporations, no matter how they view themselves), classical questions concerning freedom, democracy, state and politics in my view may require a radical reformulation. The key question would be about the chances of a new social justice and the possibility of accepting a new social contract in the situation in which the connections between the nation-state and society are becoming weaker and the choices made by traditional politics of the state are being replaced by non-governmental choices of an increasingly economic character. Ulrich Beck, an influential German sociologist, warns us that in the case of globalization “everything we have is at stake. Political freedom and democracy in Europe are at stake”. In the face of globalization on the one hand and the cultural passage to the late modernity on the other, the questions about the decline of the nation-state are asked continuously by sociologists, political scientists, philosophers, economists or historians.
Keywords: globalization; freedom; what is globalization; Ulrich Beck; Zygmunt Bauman; the retreat of the state; the university and the state; global capitalism; international integration; global welfare state; welfare state; nation-state; economic integration; the global age; global transformations; globalists; globalization and the state; transnational organizations; transnational corporations; TNCs; new social contract; modernity; second modernity; risk society